Comparative attitude and plans of the medical students and young Nepalese doctors - Lakhey, M; Lakhey, S; Niraula, SR; Jha, D; Pant, R (Kathmandu University Medical Journal, 2010)
Introduction: Many doctors are leaving Nepal to work abroad. To understand this problem better, we decided to study the attitude and plans of young doctors and medical students. Materials and methods: This cross-sectional study was conducted at Kathmandu Medical College involving 65 firstyear medical students, 100 interns and 100 house officers. The data collected was entered in Microsoft excel and analysed by SPSS (Statistical Package for Social Sciences) programme. Chi-square test was used to compare two proportions. Significance level was set at 5%. Results: Only 2% house officers said that their job prospects were excellent as compared to 22.4% of students, whereas 20% house officers as compared to 9% students thought job prospects in Nepal were poor (p= 0.003). Eighty two percent of students thought that a doctor's service to his country was very important as compared to 51% of interns (p=‹ 0.001) and 58% of house officers. Forty percent of students, 58% of interns and 48% of house officers (no statistical significance between the three groups) planned to migrate to a developed country after graduation. Eighty eight percent of students, 89% interns and 74% of house officers (no statistical significant differences between the three groups) were of the opinion that improving career opportunities or working environment of the doctor could make the profession more attractive. Conclusion: Although majority of students, interns and house officers were of the opinion that a doctor's service to his community/country was very important, almost half of them still planned to migrate to a developed country after graduation. Improving the chances of professional advancement and professional working environment can make the profession more attractive, and therefore, may decrease this tendency for brain drain from our country. Key words: Attitude; medical students; migration; young doctors; statistical significance. DOI: 10.3126/kumj.v7i2.2717 Kathmandu University Medical Journal (2009) Vol.7, No.2 Issue 26, 177-182